EFFECT OF FMCG PRODUCT PACKAGING TO CONSUMER PURCHASE DECISION - Alyaningtyas, Farah; Fachira, Ira (Journal of Business and Management, 2017)
Abstract. Indonesia’s Fast Moving Consumer Goods (FMCG) industry is considered to be one of the most attractive industries with over USD 10 billion in sales. As the competition is become more stringent, marketers began to use packaging as a marketing communication and promotion tools and pay more attention to the element of packaging that would attract customer and affecting their purchase decision. This research aims to explore the elements of packaging which have the most significant part on impacting consumers purchase decision. The element of packaging examined in this research are packaging color, background image, packaging material, packaging design, printed information, and innovation. The data for this research were collected by distributing the questionnaire to a required respondents. The result show that there is a significant effect between the element of packaging to consumer purchase decision. From six packaging element, packaging material and printed information is believed as the most significance elements on impacting consumer purchase decision. All the marketers should pay attention for a good quality of packaging and set the packaging standard and implement it for a better protection and promotion for a product. Keywords: Packaging, Purchase Decision, FMCG product, Packaging Design, Element of Packaging